Evaluation of a new image‐enhanced endoscopic technology using band‐limited light for detection of esophageal squamous cell carcinoma. Issue 2 (29th April 2013) - Kodashima, Shinya; Fujishiro, Mitsuhiro; Ono, Satoshi; Niimi, Keiko; Mochizuki, Satoshi; Asada‐Hirayama, Itsuko; Konno‐Shimizu, Maki; Matsuda, Rie; Minatsuki, Chihiro; Nakayama, Chiemi; Takahashi, Yu; Sakaguchi, Yoshiki; et al.
<x xml:space="preserve">Abstract</x> Background The aim of the present study was to evaluate the clinical utility of a new image‐enhanced endoscopy (IEE) technology called optical enhancement imaging (OEI‐1, ‐2, ‐3) by quantitatively evaluating diagnostic performance in superficial esophageal squamous cell carcinoma (SCC) in order to facilitate detection and characterization of gastrointestinal tumors. Patients and Methods The study involved 10 esophageal SCC resected endoscopically at our hospital. Ex vivo observation of the boundary area between normal and SCC was done using each mode (white light image [WLI], OEI‐1, OEI‐2, and OEI‐3) with and without magnification. The additional effect of OEI on WLI was evaluated by calculating the color difference (expressed as ΔE94) between SCC and normal epithelium, and that between the intraepithelial papillary capillary loop (IPCL) and inter‐vascular background coloration (IVBC). Results Mean ΔE94 values between SCC and normal epithelium for WLI, OEI‐1, OEI‐2, and OEI‐3 were 9.37 ± 4.64, 13.82 ± 4.46, 13.26 ± 4.73, and 16.44 ± 4.83, respectively; the corresponding values between IPCL and IVBC were 17.57 ± 10.17, 29.32 ± 9.95, 25.41 ± 11.72, and 23.71 ± 11.58, respectively. Compared with WLI, all OEI exhibited significant additional effect on ΔE94. Furthermore, we found significant additional effect of OEI‐3 in observing SCC and normal epithelium, and of OEI‐1 in observing IPCL and IVBC, compared with other OEI. Conclusion These results suggest that OEI improves endoscopic detection and characterization of esophageal SCC compared with WLI. Moreover, the data indicate that OEI‐3 is useful for detection and OEI‐1 is useful for characterization of esophageal SCC.